Awareness of residents’ on air pollution in residential area adjacent industrial area / Mohd Zulfahmi Mahsim - Mahsim, Mohd Zulfahmi (2012)
Air is the valuable sources for human. Air composition is a mixture of several gases that are nitrogen, oxygen, and various other gases. Normally human can live about three minutes only without oxygen. Air become pollute when it is mixture with contaminated air that have been produce by human activity. In this study, the author will do the an investigation on awareness of air pollution in residential area nearby industrial area. The objectives of study are to identify the awareness of residents about air pollution, to identify impact of the air pollution and to identify the law and regulation that related in controlling development in residential area. In Malaysia Environmental Quality Report 2010, the air quality in Shah Alam is poor. The research methods for this study are interview and questionnaire. The analysis of this study is the residents that live nearby factories are aware of the air pollution that caused by the factory. However, some of them lack of knowledge about the sickness that can be caused by air pollution. They only know the common sickness. Most of the resident suffering coughing and asthma which is this sickness is direct impact from the air pollution and can be called also by short-term effects. Other than that, the residents have live in dusty that caused by air pollution.